Henipaviruses-A constant threat to livestock and humans - Susann Kummer; Denise-Carina Kranz (Public Library of Science (PLoS), 2022)
In this review, we highlight the risk to livestock and humans from infections with henipaviruses, which belong to the virus family Paramyxoviridae. We provide a comprehensive overview of documented outbreaks of Nipah and Hendra virus infections affecting livestock and humans and assess the burden on the economy and health systems. In an increasingly globalized and interconnected world, attention must be paid to emerging viruses and infectious diseases, as transmission routes can be rapid and worldwide.